Method for improving the absorption rate of electromagnetic waves and electromagnetic wave absorption rate improving agent
Patent Information
- Application Number
- JP2026174242
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-16
AI Technical Summary
【0006】 本発明により、熱可塑性樹脂と導電性物質を含む樹脂組成物の電磁波の吸収率を向上させる方法および電磁波吸収率向上剤を提供可能になった。
Smart Images

Figure 2026169235000001 
Figure 2026169235000002 
Figure 2026169235000003
Abstract
Description
Technical Field
[0001] The present invention relates to a method for improving the electromagnetic wave absorptivity and an agent for improving electromagnetic wave absorptivity.
Background Art
[0002] Millimeter-wave radars transmit radio waves in the millimeter-wave band with a frequency of 30 to 300 GHz, particularly 60 to 90 GHz and a wavelength of 1 to 10 mm, and receive reflected waves that return after colliding with an object, thereby detecting the presence of obstacles, the distance to the target object, and the relative speed. The use of millimeter-wave radars is being studied in a wide range of fields such as automotive collision prevention sensors, autonomous driving systems, road information provision systems, security systems, and medical / nursing care devices. As such a resin composition for millimeter-wave radars, the one described in Patent Document 1 is known. Further, Patent Document 2 discloses a multifunctional resin composition that can be used for electromagnetic interference shielding or radio frequency interference shielding.
Prior Art Documents
Patent Documents
[0003]
Patent Document 1
Patent Document 2
Summary of Invention
Problems to be Solved by the Invention
[0004] Here, in millimeter-wave radars, transmitted electromagnetic waves are the largest cause of malfunctions. Therefore, a resin composition with high electromagnetic wave absorptivity is demanded. The present invention is made to solve such a problem, and aims to provide a method for improving the electromagnetic wave absorptivity of a resin composition containing a thermoplastic resin and a conductive substance, and an agent for improving electromagnetic wave absorptivity.
Means for Solving the Problems
[0005] Based on the above-mentioned problems, the inventors conducted research and found that in a resin composition containing a thermoplastic resin and a conductive substance, the electromagnetic wave absorption rate can be improved by improving the dispersibility of the conductive substance. Specifically, the above problem was solved by the following means. <1> A method for improving the electromagnetic wave absorption rate of a resin composition comprising a thermoplastic resin and a conductive substance, the method comprising blending a dispersant with the thermoplastic resin and the conductive substance and melt-kneading them together. <2> The thermoplastic resin includes polybutylene terephthalate resin. <1> A method for improving the absorption rate of electromagnetic waves as described above. <3> The conductive material includes carbon nanotubes. <1> or <2> A method for improving the absorption rate of electromagnetic waves as described above. <4> The dispersant contains glass fibers, <1> ~ <3> A method to improve the absorption rate of electromagnetic waves as described in one of the following. <5> The thermoplastic resin comprises polybutylene terephthalate resin, the conductive material comprises carbon nanotubes, and the dispersant comprises glass fibers. <1> A method for improving the absorption rate of electromagnetic waves as described above. <6> The mass ratio of the conductive substance to the dispersant in the resin composition is 1:1 to 200. <1> ~ <5> A method to improve the absorption rate of electromagnetic waves as described in one of the following. <7> The content of the conductive substance in the resin composition is 0.01 to 10.0 parts by mass per 100 parts by mass of the thermoplastic resin. <1> ~ <6> A method to improve the absorption rate of electromagnetic waves as described in one of the following. <8> The amount of dispersant in the resin composition is 0.01 to 100.0 parts by mass per 100 parts by mass of the thermoplastic resin. <1> ~ <7> A method to improve the absorption rate of electromagnetic waves as described in one of the following. <9> The conductive material is melt-kneaded with the thermoplastic resin in a masterbatch state. <1> ~ <8> A method to improve the absorption rate of electromagnetic waves as described in one of the following. <10> An electromagnetic wave absorption rate enhancer for a resin composition comprising a thermoplastic resin and a conductive substance, wherein the electromagnetic wave absorption rate enhancer improves the dispersibility of the conductive substance when the thermoplastic resin and the conductive substance are melt-kneaded together. <11> The thermoplastic resin comprises polybutylene terephthalate resin, and the conductive material comprises carbon nanotubes. <10> The electromagnetic wave absorption rate enhancer described above. <12> The mass ratio of the carbon nanotubes to the dispersant during the melt-kneading process is 1:1 to 200. <10> or <11> The electromagnetic wave absorption rate enhancer described above. <13> The conductive material is melt-kneaded with the thermoplastic resin in a masterbatch state. <10> ~ <12> An electromagnetic wave absorption rate enhancer listed in any one of the following. [Effects of the Invention]
[0006] The present invention makes it possible to provide a method for improving the electromagnetic wave absorption rate of a resin composition containing a thermoplastic resin and a conductive substance, and an electromagnetic wave absorption rate improving agent. [Modes for carrying out the invention]
[0007] The following describes in detail embodiments for carrying out the present invention (hereinafter simply referred to as "this embodiment"). Note that the following embodiment is illustrative for explaining the present invention, and the present invention is not limited to this embodiment. In this specification, "~" is used to mean that the numbers before and after it are included as the lower and upper limits, respectively. In this specification, all physical properties and characteristic values shall be those at 23°C unless otherwise specified. In this specification, the weight-average molecular weight and number-average molecular weight are polystyrene-equivalent values measured by GPC (gel permeation chromatography). In this specification, the units for reflection loss and transmission loss are "dB" (decibels). If the standards described herein differ in measurement methods, etc., from year to year, unless otherwise specified, the standards as of January 1, 2021 shall apply.
[0008] The method for improving the electromagnetic wave absorption rate of this embodiment is a method for improving the electromagnetic wave absorption rate of a resin composition containing a thermoplastic resin and a conductive substance, characterized by including the compounding of a dispersant with the thermoplastic resin and the conductive substance and melt-kneading them together. By adopting such a configuration, the electromagnetic wave absorption rate can be improved. The reason for this is presumed to be as follows: It was hypothesized that when conductive material is sufficiently dispersed in thermoplastic resin, the absorption rate of electromagnetic waves improves. More specifically, it was hypothesized that when conductive material is relatively abundant on the surface of the molded body, electromagnetic waves have difficulty penetrating into the molded body. On the other hand, it was hypothesized that when there is little conductive material near the interface between air and resin, electromagnetic waves can easily penetrate into the molded body, and the conductive material present inside the molded body can convert the electromagnetic waves into energy. In this embodiment, it was hypothesized that by adding a dispersant during the melt-kneading of the thermoplastic resin and conductive material, the apparent viscosity of the resin composition is increased, and the resin temperature is raised, making it easier for shear to occur in the extruder, and thus easier for the conductive material to be kneaded. It was also found that conductive material tends to aggregate in thermoplastic resin, and even when raw materials are supplied to the extruder in uniform amounts, the conductive material in the resulting pellets (resin composition) is often not uniform. In this embodiment, it was hypothesized that such aggregation can be suppressed by melt-kneading thermoplastic resin and conductive material with a dispersant, and thus the present invention was completed.
[0009] First, the resin composition used in this embodiment will be described. The resin composition in this embodiment includes a thermoplastic resin and a conductive substance. Furthermore, the resin composition in this embodiment also includes a dispersant that is added during melt kneading.
[0010] <Thermoplastic resin> The thermoplastic resins used in this embodiment are preferably polyester resins (thermoplastic polyester resins); polyamide resins; polycarbonate resins; polystyrene resins; polyolefin resins such as polyethylene resins, polypropylene resins, and cyclic cycloolefin resins; polyacetal resins; polyimide resins; polyetherimide resins; polyurethane resins; polyphenylene ether resins; polyphenylene sulfide resins; polysulfone resins; polymethacrylate resins; and are more preferably selected from polyester resins, polycarbonate resins, and polyamide resins, even more preferably containing polyester resins, and even more preferably containing polybutylene terephthalate resins.
[0011] The following describes the details of each thermoplastic resin.
[0012] <<Polyester resin>> As the polyester resin, known thermoplastic polyester resins can be used, with polyethylene terephthalate resin and polybutylene terephthalate resin being preferred, and more preferably containing at least polybutylene terephthalate resin. The polybutylene terephthalate resin used in the resin composition in this embodiment is a polyester resin having a structure in which terephthalic acid units and 1,4-butanediol units are ester-bonded, and includes, in addition to the polybutylene terephthalate resin (homopolymer), a polybutylene terephthalate copolymer containing other copolymer components other than terephthalic acid units and 1,4-butanediol units, or a mixture of the homopolymer and the polybutylene terephthalate copolymer.
[0013] Polybutylene terephthalate resin may contain one or more dicarboxylic acid units other than terephthalic acid. Specific examples of other dicarboxylic acids include aromatic dicarboxylic acids such as isophthalic acid, orthophthalic acid, 1,5-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, biphenyl-2,2'-dicarboxylic acid, biphenyl-3,3'-dicarboxylic acid, biphenyl-4,4'-dicarboxylic acid, bis(4,4'-carboxyphenyl)methane, anthracenedicarboxylic acid, and 4,4'-diphenyl ether dicarboxylic acid, alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid and 4,4'-dicyclohexyldicarboxylic acid, and aliphatic dicarboxylic acids such as adipic acid, sebacic acid, azelaic acid, and dimer acid. In the polybutylene terephthalate resin used in the present embodiment, the terephthalic acid units preferably account for 80 mol% or more of all dicarboxylic acid units, and more preferably account for 90 mol% or more.
[0014] The diol unit may contain one or two or more other diol units in addition to 1,4-butanediol. Specific examples of other diol units include aliphatic or alicyclic diols having 2 to 20 carbon atoms, bisphenol derivatives, and the like. Specific examples include ethylene glycol, propylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, decamethylene glycol, cyclohexanedimethanol, 4,4'-dicyclohexylhydroxymethane, 4,4'-dicyclohexylhydroxypropane, ethylene oxide adduct diol of bisphenol A, and the like. In addition to the above difunctional monomers, a small amount of trifunctional monomers such as trimellitic acid, trimesic acid, pyromellitic acid, pentaerythritol, and trimethylolpropane for introducing a branched structure, or monofunctional compounds such as fatty acids for molecular weight adjustment can also be used in combination in a small amount. In the polybutylene terephthalate resin used in the present embodiment, the 1,4-butanediol units preferably account for 80 mol% or more of all diol units, and more preferably account for 90 mol% or more.
[0015] As described above, the polybutylene terephthalate resin is preferably a polybutylene terephthalate homopolymer obtained by polycondensation of terephthalic acid and 1,4-butanediol. Alternatively, it may be a polybutylene terephthalate copolymer containing one or more dicarboxylic acids other than terephthalic acid as the carboxylic acid unit and / or one or more diols other than 1,4-butanediol as the diol unit. When the polybutylene terephthalate resin is a polybutylene terephthalate resin modified by copolymerization, specific preferred copolymers include polyester ether resins copolymerized with polyalkylene glycols, particularly polytetramethylene glycol, dimer acid copolymerized polybutylene terephthalate resins, and isophthalic acid copolymerized polybutylene terephthalate resins. Among these, it is preferable to use a polyester ether resin copolymerized with polytetramethylene glycol. These copolymers refer to those with a copolymerization amount of 1 mol% or more and less than 50 mol% of the total segments of the polybutylene terephthalate resin. In particular, the copolymerization amount is preferably 2 mol% or more and less than 50 mol%, more preferably 3 to 40 mol%, and even more preferably 5 to 20 mol%. Such copolymerization ratios tend to improve fluidity, toughness, and tracking resistance, and are therefore preferable.
[0016] The amount of terminal carboxyl groups in polybutylene terephthalate resin can be appropriately selected and determined, but is usually 60 eq / ton or less, preferably 50 eq / ton or less, and more preferably 30 eq / ton or less. Keeping it below the above upper limit tends to improve alkali resistance and hydrolysis resistance. There is no specific lower limit for the amount of terminal carboxyl groups, but considering the productivity of polybutylene terephthalate resin production, it is usually 10 eq / ton or more.
[0017] The amount of terminal carboxyl groups in polybutylene terephthalate resin is measured by dissolving 0.5 g of polybutylene terephthalate resin in 25 mL of benzyl alcohol and titrating it with a 0.01 mol / L benzyl alcohol solution of sodium hydroxide. The amount of terminal carboxyl groups can be adjusted by any conventionally known method, such as adjusting polymerization conditions like the raw material ratio, polymerization temperature, and reduced pressure method during polymerization, or by reacting with a chelating agent.
[0018] The intrinsic viscosity of the polybutylene terephthalate resin is preferably 0.5 to 2.0 dL / g. From the viewpoint of moldability and mechanical properties, an intrinsic viscosity in the range of 0.6 to 1.5 dL / g is more preferable. Setting the intrinsic viscosity to 0.5 dL / g or higher tends to further improve the mechanical strength of the resulting resin composition. Furthermore, setting it to 2.0 dL / g or lower tends to further improve the fluidity of the resin composition and thus improve moldability. The intrinsic viscosity of polybutylene terephthalate resin is measured at 30°C in a 1:1 (mass ratio) mixed solvent of tetrachloroethane and phenol.
[0019] Polybutylene terephthalate resin can be produced by melt polymerization of a dicarboxylic acid component mainly composed of terephthalic acid or ester derivatives thereof, and a diol component mainly composed of 1,4-butanediol, in a batch or continuous manner. Furthermore, after producing a low molecular weight polybutylene terephthalate resin by melt polymerization, the degree of polymerization (or molecular weight) can be increased to a desired value by further solid-phase polymerization under a nitrogen atmosphere or reduced pressure. The polybutylene terephthalate resin is preferably obtained by a manufacturing method in which a dicarboxylic acid component mainly composed of terephthalic acid and a diol component mainly composed of 1,4-butanediol are continuously melt-polycondensed.
[0020] The catalyst used in carrying out the esterification reaction may be one of the conventionally known ones, such as titanium compounds, tin compounds, magnesium compounds, and calcium compounds. Among these, titanium compounds are particularly preferred. Specific examples of titanium compounds as esterification catalysts include titanium alcoholates such as tetramethyl titanate, tetraisopropyl titanate, and tetrabutyl titanate, and titanium phenolates such as tetraphenyl titanate.
[0021] In addition to the above, the description in paragraphs 0013 to 0016 of Japanese Patent Publication No. 2010-174223 can be given to the polyester resin, and its contents are incorporated herein by reference.
[0022] <<Polycarbonate resin>> Polycarbonate resin is a branched homopolymer or copolymer obtained by reacting a dihydroxy compound, or a small amount thereof, with a polyhydroxy compound with phosgene or a diester carbonate. The method for producing polycarbonate resin is not particularly limited, and conventionally known methods such as the phosgene method (interfacial polymerization) or the melting method (transesterification) can be used.
[0023] As the raw material dihydroxy compound, aromatic dihydroxy compounds are preferred, including 2,2-bis(4-hydroxyphenyl)propane (=bisphenol A), tetramethylbisphenol A, bis(4-hydroxyphenyl)-p-diisopropylbenzene, hydroquinone, resorcinol, 4,4-dihydroxydiphenyl, and others, with bisphenol A being preferred. In addition, compounds in which one or more tetraalkylphosphonium sulfonates are bonded to the above aromatic dihydroxy compounds can also be used.
[0024] Among the polycarbonate resins mentioned above, aromatic polycarbonate resins derived from 2,2-bis(4-hydroxyphenyl)propane, or aromatic polycarbonate copolymers derived from 2,2-bis(4-hydroxyphenyl)propane and other aromatic dihydroxy compounds are preferred. Alternatively, copolymers mainly composed of aromatic polycarbonate resins, such as copolymers with polymers or oligomers having a siloxane structure, may also be used. Furthermore, two or more of the above-mentioned polycarbonate resins may be mixed and used.
[0025] To adjust the molecular weight of polycarbonate resin, monovalent aromatic hydroxy compounds can be used, such as m- and p-methylphenol, m- and p-propylphenol, p-tert-butylphenol, and p-long-chain alkyl-substituted phenols.
[0026] The viscosity-average molecular weight (Mv) of the polycarbonate resin is preferably 5,000 or more, more preferably 10,000 or more, and even more preferably 13,000 or more. Using a resin with a viscosity-average molecular weight of 5,000 or more tends to improve the mechanical strength of the resulting resin composition. Furthermore, the viscosity-average molecular weight (Mv) of the polycarbonate resin is preferably 60,000 or less, more preferably 40,000 or less, and even more preferably 30,000 or less. Using a resin with a viscosity-average molecular weight of 60,000 or less tends to improve the fluidity of the resin composition and improve its moldability. When the mixture contains two or more types of polycarbonate resin, it is preferable that the mixture satisfies the above range (the same consideration applies to molecular weight below).
[0027] In this embodiment, the viscosity-average molecular weight (Mv) of the polycarbonate resin is calculated using an Ubbelohde viscometer to determine the intrinsic viscosity ([η]) of the methylene chloride solution of the polycarbonate resin at 20°C, and the value is derived from Schnell's viscosity formula. [η] = 1.23 × 10 -4 Mv0.83
[0028] The method for producing the polycarbonate resin is not particularly limited, and polycarbonate resin produced by either the phosgene method (interfacial polymerization method) or the melting method (transesterification method) can be used. Furthermore, polycarbonate resin produced by the melting method and then subjected to post-treatment to adjust the amount of terminal OH groups is also preferred.
[0029] <<Polyamide resin>> The polyamide resin is a polymer whose constituent units are acid amides obtained by ring-opening polymerization of lactams, polycondensation of aminocarboxylic acids, or polycondensation of diamines and dibasic acids, and may be an aliphatic polyamide resin or a semi-aromatic polyamide resin. Specifically, examples include polyamides 6, 11, 12, 46, 66, 610, 612, 6I, 6 / 66, 6T / 6I, 6 / 6T, 66 / 6T, 66 / 6T / 6I, 9T, 10T, xylylenediamine-based polyamide resins (details to be described later), polytrimethylhexamethylene terephthalamide, polybis(4-aminocyclohexyl)methanedodecamamide, polybis(3-methyl-4-aminocyclohexyl)methanedodecamamide, and polyundemethylenehexahydroterephthalamide. Note that "I" indicates the isophthalic acid component and "T" indicates the terephthalic acid component. Furthermore, for polyamide resins, reference can be made to paragraphs 0011-0013 of Japanese Patent Application Publication No. 2011-132550, which are incorporated herein by reference.
[0030] The polyamide resin used in this embodiment is composed of diamine-derived structural units and dicarboxylic acid-derived structural units, and a xylylenediamine-based polyamide resin is preferred in which 50 mol% or more of the diamine-derived structural units are derived from xylylenediamine. More preferably, 70 mol% or more, even more preferably 80 mol% or more, even more preferably 90 mol% or more, and even more preferably 95 mol% or more of the diamine-derived structural units of the xylylenediamine-based polyamide resin are derived from at least one of meta-xylylenediamine and para-xylylenediamine. More preferably, 50 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, even more preferably 90 mol% or more, and even more preferably 95 mol% or more, the dicarboxylic acid-derived structural units of the xylylenediamine-based polyamide resin are derived from α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms. α,ω-linear aliphatic dibasic acids having 4 to 20 carbon atoms can be suitably used, such as adipic acid, sebacic acid, suberic acid, dodecanediic acid, and eicodionic acid, with adipic acid and sebacic acid being more preferred.
[0031] Diamines other than meta-xylylenediamine and para-xylylenediamine that can be used as raw material diamine components for xylylenediamine-based polyamide resins include aliphatic diamines such as tetramethylenediamine, pentamethylenediamine, 2-methylpentanediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, dodecamethylenediamine, 2,2,4-trimethyl-hexamethylenediamine, and 2,4,4-trimethylhexamethylenediamine, as well as 1,3-bis( Examples include alicyclic diamines such as aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminomethyl)decalin, and bis(aminomethyl)tricyclodecane, as well as aromatic ring-containing diamines such as bis(4-aminophenyl) ether, paraphenylenediamine, and bis(aminomethyl)naphthalene. One or more of these can be used in combination.
[0032] Examples of dicarboxylic acid components other than the above-mentioned α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms include phthalate compounds such as isophthalic acid, terephthalic acid, and orthophthalic acid, and isomers of naphthalenedicarboxylic acids such as 1,2-naphthalenedicarboxylic acid, 1,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 1,7-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and 2,7-naphthalenedicarboxylic acid. One or more of these can be used in combination.
[0033] <<Polystyrene resin>> Examples of polystyrene resins include homopolymers of styrene monomers and copolymers of styrene monomers and monomers copolymerizable with styrene monomers. Examples of styrene monomers include styrene, α-methylstyrene, chlorostyrene, methylstyrene, and tert-butylstyrene. In this embodiment, the styrene resin contains styrene monomers at a concentration of 50 mol% or more of the monomer units. More specifically, polystyrene-based resins include polystyrene resin, acrylonitrile-styrene copolymer (AS resin), high-impact polystyrene resin (HIPS), acrylonitrile-butadiene-styrene copolymer (ABS resin), acrylonitrile-acrylic rubber-styrene copolymer (AAS resin), acrylonitrile-styrene-acrylic rubber copolymer (ASA resin), acrylonitrile-ethylene propylene-rubber-styrene copolymer (AES resin), styrene-IPN type rubber copolymer, and other resins. In this embodiment, the styrene-based resin is preferably acrylonitrile-styrene copolymer (AS resin), high-impact polystyrene resin (HIPS), acrylonitrile-butadiene-styrene copolymer (ABS resin), acrylonitrile-acrylic rubber-styrene copolymer (AAS resin), acrylonitrile-styrene-acrylic rubber copolymer (ASA resin), acrylonitrile-ethylene propylene rubber-styrene copolymer (AES resin), or styrene-IPN type rubber copolymer, more preferably high-impact polystyrene resin (HIPS), and even more preferably butadiene rubber-containing polystyrene.
[0034] When a polystyrene resin contains rubber components, the content of rubber components in the polystyrene resin is preferably 3 to 70% by mass, more preferably 5 to 50% by mass, and even more preferably 7 to 30% by mass. A rubber component content of 3% by mass or more tends to improve impact resistance, while a content of 50% by mass or less tends to improve flame retardancy, which is preferable. Furthermore, the average particle size of the rubber components is preferably 0.05 to 10 μm, more preferably 0.1 to 6 μm, and even more preferably 0.2 to 3 μm. An average particle size of 0.05 μm or more tends to improve impact resistance, while an average particle size of 10 μm or less tends to improve appearance, which is preferable.
[0035] The weight-average molecular weight of polystyrene resins is typically 50,000 or more, preferably 100,000 or more, more preferably 150,000 or more, and also typically 500,000 or less, preferably 400,000 or less, and more preferably 300,000 or less. The number-average molecular weight is typically 10,000 or more, preferably 30,000 or more, more preferably 50,000 or more, and also preferably 500,000 or less, and more preferably 300,000 or less.
[0036] The melt flow rate (MFR) of polystyrene resins, measured in accordance with JIS K7210 (temperature 200°C, load 5 kgf), is preferably 0.1 to 30 g / 10 min, and more preferably 0.5 to 25 g / 10 min. When the MFR is 0.1 g / 10 min or higher, fluidity tends to improve, and when it is 30 g / 10 min or lower, impact resistance tends to improve.
[0037] Known methods for producing such polystyrene resins include emulsion polymerization, solution polymerization, suspension polymerization, and bulk polymerization.
[0038] In this embodiment, the content of thermoplastic resin in the resin composition is preferably 30% by mass or more, more preferably 35% by mass or more, even more preferably 40% by mass or more, even more preferably 45% by mass or more, and even more preferably 50% by mass or more. Setting it above the lower limit tends to further improve fluidity during injection molding. Furthermore, the content of thermoplastic resin in the resin composition is more preferably 96% by mass or less, even more preferably 93% by mass or less, and may be 90% by mass or less. Setting it below the upper limit tends to further improve the mechanical strength of the resulting molded article. The resin composition in this embodiment may contain only one type of thermoplastic resin, or it may contain two or more types. If it contains two or more types, it is preferable that the total amount is within the above range.
[0039] <Conductive material> The resin composition in this embodiment includes a conductive substance. The inclusion of a conductive substance improves the electromagnetic wave absorption rate of the resulting molded article. Examples of conductive materials used in this embodiment include metals, metal oxides, conductive carbon compounds, and conductive polymers, with conductive carbon compounds being preferred. Examples of metals include copper, nickel, silver, and stainless steel, with metal fillers, stainless steel fibers, and magnetic fillers being preferred. Examples of metal oxides include alumina and zinc oxide, with alumina fibers and zinc oxide nanotubes being preferred. Preferred conductive carbon compounds include carbon black, graphene, graphite, fullerene, carbon nanocoils, carbon nanotubes, and carbon fibers, with carbon nanotubes being more preferred. Fibers coated with metals, metal oxides, or conductive carbon compounds are also preferred. Examples include carbon-coated potassium titanate whiskers and metal-coated fibers.
[0040] In this embodiment, the conductive material is preferably in a relatively thin and long shape, such as fibrous, tubular, or whisker-like. The diameter (number-average fiber diameter) of the conductive material is preferably 0.5 to 100 nm, and more preferably 1 to 30 nm. The aspect ratio of the conductive material is preferably 5 or higher, and more preferably 50 or higher, from the viewpoint of providing good electromagnetic wave absorption. There is no specific upper limit, but for example, it is 500 or less.
[0041] The conductive material used in this embodiment is preferably carbon nanotubes. The carbon nanotubes are single-walled carbon nanotubes and / or multi-walled carbon nanotubes, and it is preferable that they include at least multi-walled carbon nanotubes. Carbon materials having a partially carbon nanotube structure can also be used. Furthermore, the carbon nanotubes are not limited to a cylindrical shape, but may have a coiled shape in which a helix completes one turn with a pitch of 1 μm or less. Carbon nanotubes are commercially available, and examples include those from Bayer MaterialScience, NanoSil, Showa Denko Corporation, and Hyperion Catalysis International. They are also sometimes referred to as graphite fibrils or carbon fibrils.
[0042] In this embodiment, the conductive substance may be blended by masterbatch formation with a thermoplastic resin. In this case, the thermoplastic resin is selected from the thermoplastic resins described above. For example, when the main component thermoplastic resin is polybutylene terephthalate resin, the thermoplastic resin used for masterbatch formation is preferably polybutylene terephthalate resin, polystyrene resin, or polycarbonate resin, with polybutylene terephthalate resin being more preferred. When masterbatch formation is done with a thermoplastic resin, the concentration of the thermoplastic resin in the masterbatch is preferably 99% by mass or less, more preferably 95% by mass or less, preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, and even more preferably 80% by mass or more. By setting the concentration within the above upper and lower limits, the dispersibility of the main component of the conductive substance in the thermoplastic resin tends to improve. It goes without saying that the thermoplastic resin, which is the main component mentioned above, does not have to be a single type, but may be a mixture of two or more types.
[0043] In this embodiment, the content of conductive material (preferably carbon nanotubes) in the resin composition is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.10% by mass or more, may be 0.20% by mass or more, and may even be 0.40% by mass or more. Setting it above the lower limit allows for effective electromagnetic wave absorption. Furthermore, in this embodiment, the content of (preferably carbon nanotubes) in the resin composition is preferably 10.0% by mass or less, more preferably 8.0% by mass or less, even more preferably 6.0% by mass or less, even more preferably 4.0% by mass or less, even more preferably 3.0% by mass or less, may even be 2.0% by mass or less, and may even be 1.0% by mass or less. Setting it below the upper limit tends to further improve the fluidity of the resin.
[0044] The resin composition in this embodiment preferably contains a conductive substance (preferably carbon nanotubes) in an amount of 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, even more preferably 0.1 parts by mass or more, even more preferably 0.3 parts by mass or more, and even more preferably 0.4 parts by mass or more, per 100 parts by mass of the thermoplastic resin. By setting the amount above the lower limit, electromagnetic wave absorption is effectively exhibited. Furthermore, the resin composition in this embodiment preferably contains a conductive substance (preferably carbon nanotubes) in an amount of 10.0 parts by mass or less, more preferably 8.0 parts by mass or less, even more preferably 6.0 parts by mass or less, even more preferably 4.0 parts by mass or less, even more preferably 3.0 parts by mass or less, and even more preferably 2.5 parts by mass or less, and particularly preferably 1.5 parts by mass or less, per 100 parts by mass of the thermoplastic resin. Setting the amount below the upper limit tends to further improve the fluidity of the resin. The resin composition in this embodiment may contain only one conductive substance or two or more. When it contains two or more, it is preferable that the total amount is within the above range.
[0045] <Dispersant> In this embodiment, a dispersant is used. The dispersant is not particularly specified as long as it enhances the dispersibility of the conductive material during melt mixing. The dispersant may take the form of fibers, fillers, beads, etc., but fibers are preferred. If the dispersant is fibers, it may be short fibers or long fibers. The raw materials for the dispersant include inorganic materials such as glass, carbon (carbon fiber, etc.), alumina, boron, ceramics, and metals (steel, etc.), and organic materials such as plants (including kenaf, bamboo, etc.), aramid, polyoxymethylene, aromatic polyamide, poly(p-phenylenebenzobisoxazole), and ultra-high molecular weight polyethylene, with glass being preferred.
[0046] In this embodiment, the resin composition preferably contains glass fibers as a dispersant. The glass fibers are selected from glass compositions such as A glass, C glass, E glass, R glass, D glass, M glass, and S glass, with E glass (alkali-free glass) being particularly preferred. Glass fibers refer to fibrous materials whose cross-sectional shape, when cut perpendicular to the length, is circular or polygonal. Glass fibers typically have a number-average fiber diameter of 1 to 25 μm, preferably 5 to 17 μm. A number-average fiber diameter of 1 μm or more tends to improve the moldability of the resin composition. A number-average fiber diameter of 25 μm or less tends to improve the appearance of the resulting molded article and enhance its reinforcing effect. Glass fibers may be single fibers or multiple single fibers twisted together. The glass fibers may take any form, such as glass roving made by continuously winding single fibers or multiple strands twisted together, chopped strands cut to a length of 1 to 10 mm (i.e., glass fibers with a number-average fiber length of 1 to 10 mm), or milled fibers crushed to a length of approximately 10 to 500 μm (i.e., glass fibers with a number-average fiber length of 10 to 500 μm), but chopped strands cut to a length of 1 to 10 mm are preferred. Glass fibers with different forms can also be used in combination. Furthermore, glass fibers having an irregular cross-sectional shape are also preferred. This irregular cross-sectional shape refers to a flattening ratio, which is indicated by the major axis / minor axis ratio of the cross-section perpendicular to the length direction of the fiber, and is, for example, 1.5 to 10, more preferably 2.5 to 10, even more preferably 2.5 to 8, and particularly preferably 2.5 to 5.
[0047] The glass fibers may be surface-treated with, for example, silane compounds, epoxy compounds, or urethane compounds, or oxidized, in order to improve their affinity with the resin components, as long as the properties of the resin composition in this embodiment are not significantly impaired.
[0048] In this embodiment, if the resin composition contains a dispersant (preferably glass fiber), its content is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably 1.0 part by mass or more, even more preferably 5.0 parts by mass or more, and even more preferably 8.0 parts by mass or more, per 100 parts by mass of the thermoplastic resin. Setting the content above the lower limit tends to further increase the mechanical strength of the resulting molded article. Furthermore, the content of the dispersant (preferably glass fiber) is preferably 100.0 parts by mass or less, more preferably 90.0 parts by mass or less, and may be 50.0 parts by mass or less, or 20.0 parts by mass or less, per 100 parts by mass of the thermoplastic resin. Setting the content below the upper limit tends to improve the appearance of the molded article and further improve the fluidity of the resin composition.
[0049] In this embodiment, if the resin composition contains a dispersant (preferably glass fiber), its content is preferably 5.0% by mass or more, and more preferably 8.0% by mass or more, in the resin composition. Furthermore, the content of the dispersant (preferably glass fiber) is more preferably 60% by mass or less, even more preferably 50% by mass or less, and even more preferably 40% by mass or less, and particularly 30% by mass or less, in the resin composition. By keeping the content below the above upper limit, the appearance of the molded article is improved, and the fluidity of the resin composition during melting tends to improve further. The resin composition in this embodiment may contain only one type of dispersant (preferably glass fiber) or two or more types. When two or more types are included, it is preferable that the total amount is within the above range.
[0050] Furthermore, the mass ratio of the conductive substance to the dispersant in the resin composition is preferably 1:1 to 200, more preferably 1:10 to 100, and even more preferably 1:15 to 1:90. By setting the ratio within this range, a resin composition with superior electromagnetic wave absorption can be obtained.
[0051] Furthermore, it is particularly preferable that the resin composition used in this embodiment includes polybutylene terephthalate resin as the thermoplastic resin, carbon nanotubes as the conductive substance, and glass fibers as the dispersant.
[0052] Next, we will describe the melt kneading of a resin composition containing a thermoplastic resin and a conductive substance. The method for improving the electromagnetic wave absorption rate of this embodiment is a method for improving the electromagnetic wave absorption rate of a resin composition containing a thermoplastic resin and a conductive substance, and includes blending a dispersant with the thermoplastic resin and the conductive substance and melt-kneading them. By blending a dispersant and melt-kneading them in this way, the dispersibility of the conductive substance in the resin composition can be further improved. The melt-kneading is carried out in an extruder, and it is preferable that the resin composition is supplied as pellets. It is preferable that the conductive material be melt-kneaded with the thermoplastic resin in a masterbatch state. More specifically, the resin composition is produced by putting a thermoplastic resin, a conductive substance (preferably a conductive substance masterbatched with a thermoplastic resin), and a dispersant into an extruder and melt-kneading them together. Other components may be added at this time. The components may be pre-mixed and supplied to the extruder all at once, or they may be supplied to the extruder using a feeder, either without pre-mixing the components or with only some of them pre-mixed. The extruder may be a single-screw extruder or a twin-screw extruder, with a twin-screw extruder being preferred. Using a twin-screw extruder tends to allow for more uniform dispersion of the conductive material. Furthermore, when a dispersant is added, it is preferable to add the dispersant in a step after the thermoplastic resin and conductive material have been fed into the extruder. More specifically, it is preferable to supply the dispersant from a side feeder located in the middle of the extruder cylinder. For example, the thermoplastic resin and conductive material are supplied from the main feed port of the extruder, melt-kneaded in the first kneading section, and then the dispersant is supplied from a side feeder located downstream of the first kneading section, and the mixture is further melt-kneaded in the second kneading section. Furthermore, the barrel temperature during melt mixing is preferably in the range of 170 to 350°C.
[0053] <Other ingredients> The resin composition in this embodiment may contain other components as needed, as long as they do not significantly impair the desired physical properties. Examples of other components include reinforcing agents and various resin additives. The other components may be present individually, or two or more in any combination and ratio.
[0054] Examples of various resin additives include stabilizers, release agents, flame retardants, reactive compounds, pigments, dyes, UV absorbers, antistatic agents, antifogging agents, antiblocking agents, flow improvers, plasticizers, dispersants, and antibacterial agents. The resin composition in this embodiment preferably contains at least one of a stabilizer and a release agent. Specifically, as stabilizers, reference can be made to paragraphs 0046 to 0057 of Japanese Patent Publication No. 2018-070722, paragraphs 0030 to 0037 of Japanese Patent Publication No. 2019-056035, and paragraphs 0066 to 0078 of International Publication No. 2017 / 038949, the contents of which are incorporated herein by reference. Specifically, as a mold release agent, reference can be given to the descriptions in paragraphs 0115 to 0120 of Japanese Patent Publication No. 2013-007058, paragraphs 0063 to 0077 of Japanese Patent Publication No. 2018-070722, and paragraphs 0090 to 0098 of Japanese Patent Publication No. 2019-123809, the contents of which are incorporated herein by reference. The resin composition in this embodiment is prepared such that the total amount of the thermoplastic resin, conductive material, dispersant, and other selectively blended components is 100% by mass.
[0055] <Physical properties of resin compositions> In this embodiment, the resin composition is preferably one that has a high electromagnetic wave absorption rate. Specifically, the resin composition in this embodiment preferably has an absorption rate of 40.0 to 100% when molded to a thickness of 2 mm (preferably 100 mm × 100 mm × 2 mm) and determined according to formula (A) at a frequency of 76.5 GHz. Formula (A)
number
[0056] The absorption rate is preferably 50.0% or higher, more preferably 55.0% or higher, even more preferably 60.0% or higher, even more preferably 65.0% or higher, even more preferably 66.0% or higher, and even more preferably 68.0% or higher. Ideally, the upper limit is 100%, but even 90.0% or lower will sufficiently satisfy the required performance. In particular, it is preferable that the absorption rate is 10% or more higher than that of the case without a dispersant, that is, the absorption rate of the same formulation in which the dispersant is replaced with the same amount of resin [(resin composition with dispersant - resin composition without dispersant) / resin composition with dispersant] × 100 (unit: %). There is no upper limit to the rate of improvement in the absorption rate, but for example, an increase of 25% or less is practical.
[0057] In this embodiment, the resin composition is preferably low in reflectivity of electromagnetic waves. Specifically, the resin composition in this embodiment preferably has a reflectance of 40.0% or less when molded to a thickness of 2 mm (preferably 100 mm × 100 mm × 2 mm) and determined according to formula (B) at a frequency of 76.5 GHz. Formula (B)
number
[0058] The reflectance is preferably 35.0% or less, more preferably 30.0% or less, and even more preferably 26.0% or less. Ideally, the lower limit is 0%, but even if it is 5.0% or more, or even 10.0% or more, it will still sufficiently meet the required performance.
[0059] In this embodiment, the resin composition preferably has low transmittance. In this embodiment, the resin composition preferably has a transmittance of 35.0% or less when molded to a thickness of 2 mm (preferably 100 mm × 100 mm × 2 mm) and determined according to formula (C) at a frequency of 76.5 GHz. Formula (C)
number
[0060] The transmittance is preferably 30.0% or less, more preferably 20.0% or less, and even more preferably 15.0% or less. Ideally, the lower limit is 0%, but even if it is 1.0% or more, it will still sufficiently meet the required performance.
[0061] In this embodiment, it is preferable that the resin composition satisfies all of the following: the absorption rate determined according to formula (A), the reflectance determined according to formula (B), and the transmittance determined according to formula (C).
[0062] Next, I will explain electromagnetic wave absorption enhancers. The electromagnetic wave absorption rate enhancer of this embodiment is an electromagnetic wave absorption rate enhancer for a resin composition containing a thermoplastic resin and a conductive substance, which improves the dispersibility of the conductive substance when the thermoplastic resin and the conductive substance are melt-kneaded together. The preferred range of the resin composition is the same as that described above for the method of improving the absorption rate of electromagnetic waves.
[0063] In this embodiment, the molded article is formed from the resin composition. For a method of molding the resin composition in this embodiment into a molded article, refer to paragraph 0080 of Japanese Patent Application Publication No. 2021-031633, which is incorporated herein by reference. The resin composition and molded article are preferably for use as electromagnetic wave absorbers (also called electromagnetic wave absorbing members), more preferably for electromagnetic wave absorbers with a frequency of at least 60 to 90 GHz, and even more preferably for electromagnetic wave absorbers with a frequency of at least 70 to 80 GHz. Such electromagnetic wave absorbers are preferably used in radar applications. Specifically, they are used in housings, covers, etc., for millimeter-wave radar. Electromagnetic wave absorbers can be suitably used in: on-board millimeter-wave radar used in automatic brake control systems, vehicle-to-vehicle distance control systems, pedestrian accident reduction steering systems, unintended acceleration suppression systems, pedal misapplication acceleration suppression systems, approaching vehicle warning systems, lane keeping assist systems, rear-end collision prevention warning systems, parking assist systems, vehicle-around obstacle warning systems, etc.; railway and aviation millimeter-wave radar used in platform monitoring / level crossing obstacle detection systems, in-train content transmission systems, tram / railway collision avoidance systems, runway foreign object detection systems, etc.; millimeter-wave radar for traffic infrastructure such as intersection monitoring systems and elevator monitoring systems; millimeter-wave radar for various security devices; medical and nursing care millimeter-wave radar such as child and elderly monitoring systems; millimeter-wave radar for various information content transmission; and more. [Examples]
[0064] The present invention will be described in more detail below with reference to examples. The materials, amounts used, proportions, processing content, and processing procedures shown in the following examples can be modified as appropriate, as long as they do not depart from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. If the measuring instruments used in the examples are difficult to obtain due to discontinuation or other reasons, measurements can be taken using other instruments with equivalent performance.
[0065] raw material The following raw materials were used. In Table 1 below, PBT refers to polybutylene terephthalate resin, and CNT refers to carbon nanotubes (the same applies to Table 2).
[0066] [Table 1]
[0067] Examples 1-3, Comparative Example 1 <Manufacturing of resin compositions (pellets)> As shown in Table 2, each component listed in Table 1 was placed in a stainless steel tumbler and stirred and mixed for 1 hour. The resulting mixture was supplied from the main feed port to a coaxial twin-screw extruder (TEX-30α, manufactured by Japan Steel Works, Ltd., screw diameter 32 mm, L / D = 42). The barrel temperature of the first kneading section was set to 250°C for plasticization. Except for Comparative Example 1, glass fibers were supplied from the side feeder in the proportions shown in Table 2, and the barrel temperature after adding the glass fibers was set to 250°C. Melt-kneading was performed under the conditions of a discharge rate of 40 kg / h and a screw rotation speed of 200 rpm. The molten material was extruded as strands under the conditions of 4 nozzles (circular (φ4 mm), length 1.5 cm). The extruded strands were introduced into a water tank for cooling, and then inserted into a pelletizer and cut to obtain resin compositions (pellets).
[0068] <76.5GHz electromagnetic wave absorption rate, reflectance rate, transmittance rate> Using the pellets obtained above, injection molding was performed using an injection molding machine (NEX80, manufactured by Nissei Plastic Industrial Co., Ltd.) with a cylinder temperature of 260°C and a mold temperature of 80°C to obtain test specimens measuring 100 mm × 100 mm × 2 mm in thickness. Using the obtained test specimens, the absorptivity determined according to equation (A), the reflectivity determined according to equation (B), and the transmittance determined according to equation (C) at a frequency of 76.5 GHz were measured as follows. For the measurements, we used a Keysight N5252A network analyzer. Furthermore, the test specimen was positioned so that the machine direction (MD) of the injection-molded body was parallel to the electric field direction for measurement. Formula (A)
number
[0069] Formula (B)
number
[0070] Formula (C)
number
[0071] [Table 2]
[0072] As is clear from Table 2 above, the electromagnetic wave absorption rate could be increased by using the method for improving the electromagnetic wave absorption rate of the present invention (Examples 1-3). In contrast, the electromagnetic wave absorption rate was inferior when the dispersant was not included (Comparative Example 1).
Claims
1. A method for improving the electromagnetic wave absorption rate of a resin composition containing a thermoplastic resin and a conductive substance, A method for improving the absorption rate of electromagnetic waves, comprising blending a dispersant with the thermoplastic resin and the conductive substance and melt-kneading them together.
2. The method for improving the absorption rate of electromagnetic waves according to claim 1, wherein the thermoplastic resin comprises a polybutylene terephthalate resin.
3. The method for improving the absorption rate of electromagnetic waves according to claim 1 or 2, wherein the conductive material includes carbon nanotubes.
4. A method for improving the absorption rate of electromagnetic waves according to any one of claims 1 to 3, wherein the dispersant contains glass fibers.
5. The thermoplastic resin comprises a polybutylene terephthalate resin, The conductive material includes carbon nanotubes, The method for improving the absorption rate of electromagnetic waves according to claim 1, wherein the dispersant contains glass fibers.
6. A method for improving the absorption rate of electromagnetic waves according to any one of claims 1 to 5, wherein the mass ratio of the conductive substance to the dispersant in the resin composition is 1:1 to 200.
7. A method for improving the absorption rate of electromagnetic waves according to any one of claims 1 to 6, wherein the content of the conductive substance in the resin composition is 0.01 to 10.0 parts by mass per 100 parts by mass of the thermoplastic resin.
8. A method for improving the absorption rate of electromagnetic waves according to any one of claims 1 to 7, wherein the amount of dispersant in the resin composition is 0.01 to 100.0 parts by mass per 100 parts by mass of the thermoplastic resin.
9. A method for improving the absorption rate of electromagnetic waves according to any one of claims 1 to 8, comprising melt-kneading the conductive material with the thermoplastic resin in a masterbatch state.
10. An electromagnetic wave absorption rate enhancer for a resin composition containing a thermoplastic resin and a conductive substance, An electromagnetic wave absorption rate enhancer that improves the dispersibility of the conductive substance when the thermoplastic resin and the conductive substance are melt-kneaded together.
11. The thermoplastic resin comprises a polybutylene terephthalate resin, The electromagnetic wave absorption rate improving agent according to claim 10, wherein the conductive material includes carbon nanotubes.
12. The electromagnetic wave absorption rate improving agent according to claim 10 or 11, wherein the mass ratio of the carbon nanotubes to the dispersant during the melting and kneading process is 1:1 to 200.
13. The electromagnetic wave absorption rate enhancer according to any one of claims 10 to 12, wherein the conductive material is melt-kneaded with the thermoplastic resin in a masterbatch state.
Citation Information
Patent Citations
Resin composition
JP2010155993A
Millimeter wave radar-purpose cover and millimeter wave radar module including the same
JP2019197048A